KINERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN PASAMAN BARAT - Rini Novriani (Universitas Negeri Padang, 2014)
This study aimed to obtain information about the performance of employees at the Department of Education of the West Pasaman aspects of honesty, creativity, motivation, and research kedisiplinan.populasi are all employees of Education Department of West Pasaman totaling 80. Number of samples is based on table 66 krejchi, withdrawal stratied samples using proportional random sampling technique, data collection tool was a questionnaire likertyang scale model has been tested. The results of the study confirms the performance of employees at the Department of Education West Pasaman in the category quite well. Keywords: Employee Performance